Réponses

  • carys
  • Modératrice confirmée
2013-02-28T14:37:08+01:00

1) A(x) = (x - 1) (x + 1) + (x - 1)²

A(x) = x² + x - x -1 + x² - 2x + 1

A(x) = 2x² - 2x

 

2) A(x) = 2x² - 2x

A(x) = 2x(x - 1)

 

3) A((√2)/2) =  2 * (√2)/2 ((√2)/2 - 1)

A((√2)/2) = √2 ((√2)/2 - 1)

A((√2)/2) = 1 - √2

 

4) A(-(√2)/2) =  2 * (-(√2)/2) (-(√2)/2) - 1)

A((√2)/2) = -√2 (-(√2)/2) - 1)

A((√2)/2) = 1 + √2

 

5) (1 - √2) (1 + √2) = 1 + √2 - √2 - 2 = -1

 

6) • (1 - √2)² - 2 * (1 - √2) = 1² - 2*1*√2 + (√2)² - 2 + 2√2 = 1 - 2√2 + 2 - 2 + 2√2 = 1 + 2 - 2 = 1

fais la meme chose avec Q ;)

 

voilà voilà